PERBUATAN PRILAKU BULLYING MENURUT ILMU PERUNDANG UNDANGAN - Hamdani (Al Qadhi, 2023)
This study was conducted to understand the meaning process of bullying on teen’s bully. Subjects in this study consisted of adolescents aged 16-18 years who had committed bullying behavior on peers or friends of the school. Data collection techniques used were in-depth interviews. Data analysis was conducted using driven theory of thematic analysis.Based on the results of research could be concluded that bullying behaviors such as hitting and disturbing the victim, at low levels meaning, as the self-satisfaction and self-pleasure, it was derived from one of the sources of meaning that was personal relationships. Bullying behavior such as hitting and ridiculing or mocking the victim were bullying at the high level meaning, interpreted by the teen’s bully as a step to be “rulers” and the process of searching identity which was obtained from combining and integrating resources meaning, such as to meet basic needs, personal relationships, and pleasure activities.